A highly adhesive and melatonin-loaded PEG hydrogel prevents tumor recurrence and promotes wound healing for tumor-resection wound management of liposarcoma - Yonghui Liang; Jianyang Shan; Chen Tan; Zhen Pan; Zhaohui Li; Xiang Fei; Gen Wen; Qingcheng Yang; Dongdong Cheng (Materials Today Bio)
Liposarcoma is the most common soft tissue sarcoma, and the surgical resection is the primary treatment. However, liposarcoma recurrence and delayed wound healing remain critical challenges due to extensive surgical interventions. Herein, we design an injectable polyethylene glycol (PEG)-based hydrogel (PEG@MT) with high skin adhesion and loading melatonin, to concurrently prevent liposarcoma recurrence and promote postoperative wound healing. The hydrogel is formed by mixing 8-arm-polyethylene glycol-succinimidyl glutarate (8-arm-PEG-SG) and 4-arm-polyethylene glycol-amine (4-arm-PEG-NH2) at a 1:1 ratio, establishing an amide-bond crosslinked network. Excess succinimidyl ester groups bind to endogenous skin amine groups, ensuring high adhesion for effective wound closure. Functional assays demonstrated its dual functionality: promoting wound healing and angiogenesis while suppressing liposarcoma proliferation and metastasis. Mechanistically, the PEG@MT hydrogel promotes cell cycle arrest and apoptosis via FOXO pathway in liposarcoma cells. The studies also established a novel liposarcoma resection model to validate therapeutic outcomes. The PEG@MT hydrogel offers effective closure of the wound due to the high skin adhesion capacity. Meanwhile, the sustained release of melatonin in surgical wounds significantly inhibits the local recurrence of liposarcoma. Overall, the developed PEG@MT hydrogel capable of preventing recurrence of liposarcoma while promoting postoperative wound healing shows valuable application for postsurgical liposarcoma-resection wound management.